Percepciones sobre diversidad cultural y comunicación intercultural de futuros maestros - Pareja de Vicente, Dolores; Leiva Olivencia, Juan José; Matas Terrón, Antonio (Revista Electrónica Interuniversitaria de Formación del Profesorado, 2019)
Intercultural education is a topic of great social and pedagogical interest and significance in the initial training of teachers. Its impact on the university context represents an inescapable impulse to build an open mindset that respects cultural diversity as a key element that will entail a real move towards inclusion. The objective of this study has been to discover the perceptions and profile of a non-probabilistic pilot sample of university students from a Primary Education degree course towards diversity and intercultural communication. A survey design was carried out, for which an ad-hoc questionnaire was built. 62 students participated in the survey, which was completed with a simulated sample of 500 cases using the Monte Carlo procedure for data mining analysis. A descriptive analysis was performed, as well as a cluster and tree forest analysis. Ward’s method of minimal variance was applied for its ability to discriminate in determining grouping levels. The results revealed, among other things, the existence of a positive trend towards the recognition of cultural diversity as an enriching aspect in the generation of inclusive attitudes and intercultural communication. Similarly, different profiles were identified among the participants, as well as a precedence of the analysed variables that establish the distinction between profiles.